Saggi di anglistica e americanistica - Ornella, De Zordo (Strumenti per la didattica e la ricerca, 2008)
"Saggi" brings together the results of the research activity carried out on the PhD course in English and American Studies (Department of Modern Philology, University of Florence). The contributions relate to the theatre, narrative, poetry, autobiographical writing and correspondence, and range from the Renaissance up to the present day. The heterogeneity of the material illustrates the free choice of the young academics who, in the climate of collaboration that was established, decided to address the technical and editorial aspects of the book as a team in the open access editorial workshop of the Department.